2009
DOI: 10.1111/j.1365-2354.2009.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and quality of life during treatment of ocular bulb removal in individuals with uveal melanoma

Abstract: INTRODUÇÃO Apesar de uma consciência crescente, poucos são os estudos sistemá-ticos voltados para a orientação do clínico em face do impacto do câncer sobre o paciente e sobre a violência dos processos cirúrgicos decorrentes. Em oncologia, a cirurgia radical é muitas vezes necessária, mas pode levar a severos prejuízos funcionais e eventualmente estéticos (1). O presente estudo se propõe a avaliar prospectivamente pacientes, com melanoma uveal e indicação para enucleação, nos aspectos psicológicos em três mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Depression has been investigated in a recent prospective study on a sample of patients with UM after surgical treatment ( n = 20) [33]. The aim of the study was to perform a psychological assessment of patients with UM who have been referred for enucleation.…”
Section: Resultsmentioning
confidence: 99%
“…Depression has been investigated in a recent prospective study on a sample of patients with UM after surgical treatment ( n = 20) [33]. The aim of the study was to perform a psychological assessment of patients with UM who have been referred for enucleation.…”
Section: Resultsmentioning
confidence: 99%
“…MH notes the frequency of nervousness and depression versus peacefulness, happiness, and calmness [20] (for more details, see Ware et al [21]). Typically, all scores are transformed into a standardized (0-100) continuous scale, with 50 being the mean and an SD of 10 [19]. Higher scores represent better health, function, and overall quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…After surgery, the psychological impairment reaches a maximum at 3 months, when the disease-related limitations become noticeable and patients have difficulty returning to their lives [19]. Amaro et al [19] reported most affection of PF, VT, SF, and MH with a more balanced quality of life after 1 year. For irradiated patients, we found a continuous decrease in PF and RP from the first to the second follow-up, but no dip in the emotional items SF, MH, or VT.…”
Section: No Glaucoma Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of stress and depression, higher separation and divorce rates are reported in enucleated patients compared to the general population. 13,17,20 Although many of the patients in our series found post-operative pain and dissatisfaction with cosmetic appearance to be of concern in the early postoperative period, the vast majority reported overall improvement in these areas compared to their presurgical state. Intolerance of the conformer or prosthesis was reported by 33% of our patients following surgery.…”
Section: Impact Of Treatmentmentioning
confidence: 89%